Impact of active smoking on outcomes in HPV+ oropharyngeal cancer. Issue 2 (26th November 2019) - Xiao, Roy; Pham, Yvonne; Ward, Matthew C.; Houston, Narcissa; Reddy, Chandana A.; Joshi, Nikhil P.; Greskovich, John F.; Woody, Neil M.; Chute, Deborah J.; Lamarre, Eric D.; Prendes, Brandon L.; Lorenz, Robert R.; et al.
Abstract: Background: The role of smoking among patients with human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (OPSCC) is unclear. Methods: A retrospective cohort study of patients with HPV(+) OPSCC from 2001 to 2015 at a tertiary‐care institution was conducted. The primary outcome was overall survival (OS). Results: Among 484 included patients, 94 (19.4%) were active smokers, 226 (46.7%) were former smokers, and 164 (33.9%) never smoked. Among active smokers, 82 patients (87.2%) had a ≥10 pack‐year and 69 (73.4%) had a ≥20 pack‐year smoking history. After adjusting for covariates, active smoking was a significant predictor of inferior OS (HR 2.28, P  < .001) and PFS (HR 2.26, P  < .001). When including pack‐years as the covariate, ≥20 pack‐years predicted a decreased effect‐size for inferior OS and PFS. Conclusions: For patients with HPV(+) OPSCC, active smoking at diagnosis is the most powerful covariate capturing smoking history to predict OS and PFS.